Image quality evaluation for two different positron emitters in a preclinical PET scanner - Rodrigo Modesto Gadelha; Andréa Vidal Ferreira; Guilherme Albuquerque Cavalcante Souza; Juliana Batista Silva; Marcelo Mamede (Brazilian Journal of Radiation Sciences, 2020)
Positron emission tomography (PET) is widely used in preclinical trials, generating molecular images applied to biochemical, metabolic and functional investigation of organs and tissues. The positron emitters 11C and 18F radionuclides are relevant for different diseases studies. However, they have different positron energies, ranges, and branching ratio. This could result in a distinct quality between the acquired PET images. Thus, the aim of this study is to evaluate the image quality performance of the PET scanner (LabPET 4, GE) at CDTN/CNEN using the NEMA NU 4-2008 standards and specific phantom for these two different positron emitters. The NEMA image-quality (IQ) phantom consists of 3 different regions to analyze distinct characteristics: uniformity, recovery coefficients (RCs) and spill-over rations (SOR) in air and water. The IQ phantom was filled with two different aqueous solutions (18F-FDG and 11C-PK11195), both activities calibrated at the beginning of acquisition (3.7MBq). The IQ phantom was placed in the center of the field-of-view (FOV) and measured with the typical whole body imaging protocol. The images were reconstructed following the Molecular Imaging Laboratory (LIM/CDTN) standard protocol: MLEM-3D algorithm, 20 iterations, no high-resolution mode, no attenuation or scatter corrections, no post-filtering. PMOD® software was used to perform images post-processing following NEMA analyses standard. The %SD of medium concentration activity for 18F and 11C was 7.7 and 14.5, respectively. The RCs for 18F and 11C were 0.11 and 0.12 respectively for the 1-mm-diameter rod and 0.88 and 0.77 for the 5-mm-diameter rod. SORs in air were 0.19 and 0.22, respectively, and in water 0.29 and 0.33. Experimental results demonstrates that when 18F radionuclide is used, PET images presents a better performance in the image quality tests compared to 11C PET images.